2018
DOI: 10.1002/ghg.1814
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of carbon tax to stimulate CCS investment in China's coal‐fired power plants: A real options analysis

Abstract: Carbon tax is an important policy instrument to control greenhouse gases. How to design a suitable carbon tax rate is of significance for policy makers. This study aims to address this issue from a microeconomic perspective by exploring the decision behavior of a potential investor. A trinomial tree model based on real options theory is presented to evaluate carbon capture and storage (CCS) investment in coal‐fired power plants considering uncertain factors. The model is then applied to a case study and the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The cost of abatement of CCU technology is expected to be 58–68 US $/tCO 2 [43,44]. Now, the Chinese government has officially initiated the construction of a national carbon market [45], and research on promoting the development of low-carbon technologies in the high-carbon sectors by imposing carbon taxes is also being carried out simultaneously [46]. From the experience of the European Union and other foreign countries, the lime industry, which is a major greenhouse gas emitter, will be strictly constrained by the carbon emission control policy [47].…”
Section: Discussionmentioning
confidence: 99%
“…The cost of abatement of CCU technology is expected to be 58–68 US $/tCO 2 [43,44]. Now, the Chinese government has officially initiated the construction of a national carbon market [45], and research on promoting the development of low-carbon technologies in the high-carbon sectors by imposing carbon taxes is also being carried out simultaneously [46]. From the experience of the European Union and other foreign countries, the lime industry, which is a major greenhouse gas emitter, will be strictly constrained by the carbon emission control policy [47].…”
Section: Discussionmentioning
confidence: 99%
“…From carbon taxes and other policy perspectives, Wang and Zhang 25 explored the optimal carbon tax policy based on the trinomial tree real‐option mode and considered the mechanism of combining carbon tax policy and carbon trading system. And Zhang et al 26 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen, Wang, and Ye [28] studied the significance of a power generation subsidy in the investment decisions of CCS under the dual influence of the carbon trading market and subsidy policies, and found that the effects of a government subsidy on CCS investment and carbon reduction depends on market conditions. Wang and Zhang [29] pointed out that carbon tax is an important policy instrument to control greenhouse gases, and explored the decision behavior of a potential investor to design a suitable carbon tax rate from a microeconomic perspective. The results showed that the optimal carbon tax rate is sensitive to uncertainties, which includes carbon price volatility and initial carbon price.…”
Section: Literature Reviewmentioning
confidence: 99%